FUNDAMENTAL AND CLINICAL STUDIES ON DL-8280 IN THE SURGICAL FIELD - YOKOYAMA, ISAO; SAITO, TOSHIAKI; ARAI, TAKEYUKI; YAMADA, YOSHINARI; HANATANI, YUJI; FUKUTOMI, TAKASHI (CHEMOTHERAPY, 1984)
Fundamental and clinical studies on DL-8280, a newly synthesized antibacterial agent, were conducted in the surgical field. For the fundamental studies, 200 and 400mg of DL-8280 was administered orally to 10 patients with cholelithiasis 3 hours before the operations. The concentration of DL-8280 in serum was 3.10, 1.87, 1.76μg/ml (200mg), and 5.65, 4.92, 3.88μg/ml (400 mg) at 2, 4, 6 hours after adminitration, respectively. The concentration in choledochal bile was 6.35 (200 mg) and 11.3 (400 mg) μg/ml. The concentration in cholecystic bile was 11.3 (200 mg) and 16.8 (400 mg) μg/ml. The concentration of DL-8280 in bile was studied every 30 minutes after oral administration of 200 mg with food. The peak concentration of DL-8280 in bile was 7.81μg/ml, thereafter the concentration decreased slowly to 3.65, 1.58, 0.45μg/ml at 6, 12, 24 hours after administration. The recovery rate of DL-8280 into bile was 0.53%. The peak concentration of DL-8280 in bile was 1.5 times higher than that of norfloxacin (NFLX), and the recovery rate of DL-8280 was 3 times higher than that of NFLX. So, it was suggested that DL-8280 might be clinically effective, because of the high and prolonged concentration in serum and biliary system. For the clinical studies, DL-8280 was administered to 43 paients with abscess, mastitis, phlegmone, cholangitis, furuncle, carbuncle and etc. The dose of DL-8280 was 100mg×3/day to 40 patients and 200mg×3/day to 3 patients. The clinical effect of DL-8280 was good in 67.4%, fair in 20.9% and poor in 11.6%. Bacteriological effect of DL-8280 was good in 10 out of 17 (58.8%) strains of gram positive cocci, and good in 4 out of 6 (66.7%) strains of gram negative bacilli. The minimal inhibitory concentration of DL-8280 was 0.10-0.78μg/ml against 9 strains of gram positive cocci, and 0.05-0.20μg/ml against 2 strains of gram negative bacilli. Therefore, it was suggested that DL-8280 might be effective not only against infections caused by gram negative bacilli, but also against infections caused by gram positive cocci. No side effect and abnormal findings in laboratory data due to the administration of DL-8280 were experienced.